Gla portein localization and histological characterization of bone stuctures in relevant aquaculture fish - Roberto, Vania Palma (2006)
Osteocalcin (Oc) and Matrix Gia Protein (MGP) are vitamin K-dependente proteins known for their Ca2" binding capacity. Considering the problem of skeletal malformations in Mediterranean fish aquaculture, we investigated a possible correlation between vertebral deformities and changes of Oc and Mgp accumulation sites. ln this work we proposed to characterize bony and cartilaginous tissues from important fish for aquaculture, using molecular tools. The sites of gene expression and accumulation of osteocalcin and Mgp were investigated throughout Northern blot analysis and immunohistochemistry, following the cloning of those cDNAs not yet available, together with histological analysis. ln Scophthalmus maximus, oc mRNA was detected in vertebrae and branchial arches while mgp mRNA was highly expressed in branchial arches, followed by vertebrae, kidney and heart. ln S. maximus and Diplodus sargus, Mgp accumulated in chondrocytes from cartilages, in the vertebral mineralizing fronts and in notochord cells. Mgp was also found in scales of D. sargus. Ocaccumulated mainly in bone tissues, like the ceratobranchial bone and vertebral bone matrix. ln cultured Sparus aurata, Mgp accumulated mainly in vertebrae growth zones and in notochord cells while Oc was immunodetected in bone matrix of vertebrae and vertebral arches, both in non-deformed and in deformed vertebrae. We also identified Oc in the non-calcified notochord cells of deformed vertebrae, suggesting that abnormal skeletal development resulted in modifications on sites of osteocalcin expression and/or accumulation. Accordingly, histological analysis of normal and deformed vertebrae revealed calcification in blood vessel walls and pathological formation of chondroid bone, in the affected area of deformed vertebrae. Osteocalcina (Oo) e Proteína Gla da Matriz (MGP2 são proteínas dependentes da vitamina K, com capacidade para ligarem Ca2+. Considerando o problema do desenvolvimento de malformações ósseas nos peixes de aquacultura no Mediterrâneo, investigou-se a ...